Simulation of Formation of Icosahedral Structure in Solid-Liquid-Solid Phase Change Using Molecular Dynamics Methods - Nikodemus Umbu Janga Hauwali; Artoto Arkundato; Lutfi Rohman (Jurnal ILMU DASAR, 2016)
It has successfully conducted research to study the structure of the icosahedral formation in the event of change of the solid phase - liquid-solid using molecular dynamics method . The result showed that the percentage of the maximum icosahedral structure is obtained when the simulation is run at the start of the cooling temperature of 2875 K at a rate of temperature decrease of 0.064 K /step and at the beginning of the cooling temperature of 3000 K at a rate of temperature decrease 0.12 K/step. While icosahedral minimum percentage obtained when the simulation is run at a temperature of 2750 K with the initial cooling rate of temperature decrease of 0.069 K/step. Based on these results we can conclude that there is a relationship between the initial temperature of the cooling and the rate of temperature decrease of the icosahedral structure is formed. Keywords: Icosahedral, phase change, molecular dynamics